Bismuth-based adsorption material as well as preparation method and application thereof

The bismuth is loaded on activated carbon by solvent-thermal method, which solves the problem of easy agglomeration of bismuth-based adsorption materials during the preparation process, improves the adsorption performance and specific surface area, and achieves efficient gaseous iodine adsorption, and the preparation process is simple and economical.

CN119524800APending Publication Date: 2025-02-28GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411632708.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing bismuth-based adsorption materials are prone to agglomeration during the preparation process, resulting in blockage of activated carbon channels, reducing the adsorption performance of gaseous iodine, and the relationship between the modification concentration and adsorption performance is unclear.

Method used

Anhydrous ethanol is used as the solvent, ethylene glycol is used as the reducing agent, and Bi(NO3)3·5H2O is used as the modifier. The bismuth is loaded onto activated carbon by one-step synthesis method of solvent heat, avoiding the complexity and energy consumption of the pyrolysis method, and controlling the mass ratio of the bismuth modified solution to activated carbon to optimize the adsorption performance.

Benefits of technology

The specific surface area of ​​bismuth-based adsorption material and the adsorption capacity of gaseous iodine are improved, the blockage of the activated carbon pore structure is avoided, and the adsorption performance of gaseous iodine is enhanced. The preparation process is simple, cost-effective and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524800A_ABST
    Figure CN119524800A_ABST
Patent Text Reader

Abstract

The invention relates to a bismuth-based adsorption material and a preparation method and application thereof, and relates to the technical field of waste gas treatment, and a bismuth-based adsorption material finished product Bi (at) AC for adsorbing gaseous iodine is obtained through the steps of AC carrier pretreatment, homogeneous phase A liquid preparation, homogeneous phase B liquid preparation, Bi (at) AC preparation and the like. The preparation method has the advantages that absolute ethyl alcohol is used as a solvent, ethylene glycol is used as a reducing agent, Bi (NO3) 3.5 H2O is used as a modifier, a solvothermal one-step synthesis simple method is adopted, and metal active sites are provided for activated carbon through loading of a bismuth-based material in a bismuth modification mode; the original single physical adsorption of activated carbon is converted into adsorption of physical action and active site chemical action of an activated carbon pore structure, so that the adsorption performance of gaseous iodine is improved, a complex and high-energy-consumption pyrolysis method is omitted, the preparation period is short, and no toxic gas is released in the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waste gas treatment, and in particular to a bismuth-based adsorption material and a preparation method and application thereof. Background Art

[0002] Nuclear energy, as a clean and efficient energy source, is one of the effective ways to achieve my country's "dual carbon" goals. The safe handling and disposal of spent fuel is an important guarantee for the sustainable development of nuclear energy. Radioactive waste gas will be produced during the reprocessing of spent fuel. Among them, radioactive iodine is a pollutant that is of key concern in the nuclear fuel cycle, spent fuel reprocessing and radioactive waste treatment. The radioactive iodine in the environment has a long half-life, high water solubility, strong fluidity and high toxicity. Its effects on the thyroid include hypothyroidism, thyroid nodules and thyroid cancer. Therefore, radioactive iodine needs to be adsorbed and treated.

[0003] At present, a large number of adsorbents have been developed for the adsorption of radioactive gaseous iodine. For example, silver-based zeolites, metal-organic framework materials (MOFs), aerogels and other adsorbent materials have been developed for the adsorption of gaseous iodine. However, these materials are often limited in practical applications due to their preparation cost, adsorption performance, process difficulty and other issues.

[0004] Bismuth-based porous materials are an emerging iodine adsorbent in recent years. They can quickly capture iodine. Compared with other functional materials (silver-based zeolite, MOF, etc.), they have the advantages of low cost, easy synthesis, low toxicity, and high adsorption capacity. At the same time, after the adsorbent captures iodine, the BiI3 and Bi5O7I finally converted have good thermodynamic stability, making the captured iodine difficult to desorb. Therefore, we believe that bismuth-based porous materials are expected to replace the silver-based materials commonly used in the current spent fuel reprocessing process.

[0005] Activated carbon (AC) is an ideal adsorbent. For radioactive gaseous iodine, it is mainly modified with metals such as silver and bismuth to obtain metal-loaded modified activated carbon. The principle is to increase the metal active sites on the surface of activated carbon by loading metals, improve the interaction between metal groups, and transform the adsorption effect from the original single physical adsorption to physical and chemical adsorption. Xie et al. (Xie et al., 2023) prepared bismuth-loaded camphor leaf carbon with a loose structure. The Bi2O3 and carboxyl groups contained in it showed strong affinity for iodine, and the maximum adsorption capacity reached 885.8 mg / g (nearly twice that before modification).

[0006] However, bismuth-based adsorbent materials are prone to agglomeration during the preparation process, which leads to blockage of the AC pores and reduces the adsorption performance of gaseous iodine. In addition, the relationship between the modified concentration of bismuth-based materials and the adsorption performance of the final adsorbent materials for gaseous iodine also needs to be explored; therefore, bismuth-based porous materials for adsorbing gaseous iodine need further research to improve the adsorption performance of the adsorbent materials for gaseous iodine. Summary of the invention

[0007] The present invention aims to provide a bismuth-based adsorption material with abundant active sites and good adsorption performance for gaseous iodine. In order to achieve the above purpose, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a bismuth-based adsorption material, comprising the following steps:

[0009] S1, AC carrier pretreatment: weigh a certain amount of AC, wash it with deionized water, put it in an oven to dry overnight, and use a sieve to screen out particles of appropriate size to obtain AC carrier; S2, preparation of homogeneous liquid A: stir and mix anhydrous ethanol and ethylene glycol solution to obtain liquid A; S3, preparation of homogeneous liquid B: take a certain amount of Bi(NO3)3·5H2O and add it to liquid A, stir and mix to obtain liquid B; S4, preparation of Bi@AC: weigh a certain amount of AC carrier and add it to liquid B, stir and mix, and then place it in a stainless steel hydrothermal reactor, and place the reactor in an oven to react. After the reaction is completed, the reactant is obtained, and the reactant is rinsed with ultrapure water and anhydrous ethanol, and finally placed in an oven to dry, and Bi@AC is obtained after drying.

[0010] By adopting the above technical scheme, activated carbon of suitable specifications is screened as a carrier for pretreatment. The activated carbon alone relies on weak forces such as van der Waals force and electrostatic force to capture gaseous iodine, but this capture has poor stability and the iodine component is easy to escape. Anhydrous ethanol is used as a solvent, ethylene glycol is used as a reducing agent, and Bi(NO3)3·5H2O is used as a modifier. A simple solvothermal one-step synthesis method is adopted to load bismuth onto the activated carbon using the reducing property of ethylene glycol. The -COOH rich in ethylene glycol has strong reducing properties and can reduce bismuth ions in the solution to bismuth elemental bismuth. The bismuth elemental bismuth is loaded onto the pores of the activated carbon, eliminating the complex and energy-intensive pyrolysis method, and the preparation cycle is short. No toxic gas is released during the preparation process. Through the bismuth modification method, the loading of bismuth-based materials provides metal active sites for the activated carbon. When adsorbing gaseous iodine, the original single physical adsorption of the activated carbon is transformed into the physical action of the activated carbon pore structure and the adsorption of the chemical action of the active site, thereby improving the adsorption performance of gaseous iodine.

[0011] Optionally, the particle size of the AC carrier is 10 mesh.

[0012] Optionally, the usage ratio of anhydrous ethanol and ethylene glycol is 33.6:(16-17).

[0013] Optionally, the added concentration of Bi(NO3)3·5H2O is 0.004-0.005 g / ml.

[0014] Optionally, the mass ratio of the added amount of Bi(NO3)3·5H2O and the AC carrier is 1:(5-20).

[0015] Optionally, the mass ratio of the added amount of Bi(NO3)3·5H2O and the AC carrier is 1:10.

[0016] Optionally, the stirring condition in S3 is magnetic stirring at room temperature for 30 minutes at a rotation speed of 500 rpm. The stirring condition in S4 is magnetic stirring at room temperature for 1 hour.

[0017] Optionally, the reaction conditions in S4 are 200° C. for 6 hours, and the drying temperature is 60° C.

[0018] By adopting the above technical scheme, the concentration of bismuth-modified solution will affect its loading amount on activated carbon, optimize and control the solvothermal preparation process, improve the agglomeration phenomenon of bismuth-based materials, avoid the blockage of activated carbon pore structure, and improve the specific surface area and iodine adsorption capacity of Bi@AC.

[0019] The present invention also provides a bismuth-based adsorption material prepared by the preparation method described in the above technical solution.

[0020] The present invention also provides the use of the bismuth-based adsorption material of the above technical solution in adsorbing gaseous iodine.

[0021] By adopting the above technical scheme, the bismuth-based adsorption material has good adsorption performance for gaseous iodine. The adsorption capacity of activated carbon for gaseous iodine is enhanced by bismuth modification. Compared with silver-based zeolite, metal-organic framework or other gaseous iodine adsorption materials, bismuth-based materials and activated carbon are more economical, and the prepared Bi@AC gaseous iodine adsorption capacity is higher than that of general silver-based zeolite.

[0022] In summary, the present application includes at least one of the following beneficial technical effects:

[0023] 1. Anhydrous ethanol is used as solvent, ethylene glycol is used as reducing agent, Bi(NO3)3·5H2O is used as modifier, and a simple solvothermal one-step synthesis method is adopted. The reducing property of ethylene glycol is utilized to load bismuth onto activated carbon. The -COOH rich in ethylene glycol has strong reducing property and can reduce bismuth ions in the solution into bismuth element, which is then loaded onto the pores of activated carbon. The complex and energy-intensive pyrolysis method is omitted, the preparation cycle is short, and no non-toxic and harmless gas is released during the preparation process, thereby improving the convenience of preparing bismuth-based adsorbent materials.

[0024] 2. Through bismuth modification, the bismuth-based material load provides metal active sites for activated carbon. When adsorbing gaseous iodine, the original single physical adsorption of activated carbon is transformed into the physical action of the activated carbon pore structure and the adsorption of the chemical action of the active site, thereby improving the adsorption performance of gaseous iodine.

[0025] 3. Compared with silver-based zeolites, metal-organic frameworks or other gaseous iodine adsorption materials, bismuth-based materials and activated carbon are more economical, and the prepared Bi@AC has a higher gaseous iodine adsorption capacity than general silver-based zeolites.

[0026] 4. The solvothermal method used in this application successfully loaded Bi onto activated carbon, and the controllable preparation of Bi@AC with different proportions can be achieved by adjusting the mass ratio of bismuth-modified solution to activated carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 (a) is a graph showing the relationship between the adsorption time and the adsorption capacity of Bi@AC prepared in Examples 1-3 and Comparative Examples 1-2 and AC of Comparative Example 3 in a gaseous iodine adsorption test, Figure 1 (b) is a graph showing the adsorption of gaseous iodine by the products of Examples 1-3 and Comparative Examples 1-3 in the present application, Figure 1 (c) is a graph showing the adsorption of gaseous iodine by Bi@AC prepared in Examples 4-8 of the present application;

[0028] Figure 2 (a) is the XRD spectrum of Bi@AC prepared in Example 1 and AC prepared in Comparative Example 1 of the present application, Figure 2 (b) is the XRD pattern of Bi@AC prepared in Examples 1-3 and Comparative Examples 1-2 of the present application;

[0029] Figure 3 (a, b) are SEM images of AC of Comparative Example 3 in this application, Figure 3 (c) is a SEM cross-sectional image of AC of Comparative Example 3 in this application, Figure 3 (d, e, f) are SEM images of Bi@AC in this application. Figure 3 (g, h, i) are elemental mapping images of Bi@AC in this application;

[0030] Figure 4 (a) is a SEM image of Bi@AC before adsorption of gaseous iodine in this application. Figure 4 (b) is a SEM image of Bi@AC after adsorption of gaseous iodine in this application;

[0031] Figure 5 This is the energy dispersion spectrum of Bi@AC after adsorption of gaseous iodine in this application;

[0032] Figure 6 It is the Fourier transform infrared spectra of AC of comparative example 3 and Bi@AC prepared in example 1 in the present application;

[0033] Figure 7 It is the FTIR spectra of Bi@AC before and after adsorption of gaseous iodine in this application;

[0034] Figure 8 is the XPS spectrum of Bi@AC in this application;

[0035] Fig. 9 (a) is a N2 adsorption-desorption isotherm curve of AC of Comparative Example 3 in the present application, Fig. 9 (b) is the N2 adsorption-desorption isotherm of Bi@AC prepared in Example 1. Fig. 9 (c, d) are the pore size distribution curves of AC and Bi@AC calculated by the BJH model;

[0036] Fig.10 (a) is a diagram showing the fitting results of the pseudo-first-order kinetic model and the pseudo-second-order kinetic model for the adsorption of gaseous iodine by Bi@AC prepared in Example 1 of the present application, Fig.10 (b) is a Langmuir and Freundlich isotherm model fitting result diagram of the Bi@AC adsorbing gaseous iodine prepared in Example 1 of the present application;

[0037] Fig.11 It is the thermogravimetric analysis diagram of AC and Bi@AC before and after adsorption of gaseous iodine in this application. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the following embodiments and appended Figure 1-11 , the present invention is further described in detail. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art who make modifications or equivalent substitutions based on their understanding of the technical solution of the present invention, without departing from the spirit and scope of the technical solution of the present invention, should all be included in the protection scope of the present invention.

[0039] The information of reagents, instruments and equipment used in the following examples is shown in Tables 1.1 and 1.2. All reagents and chemicals were used as they are without further treatment. Other specific conditions not specified were carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0040] Table 1.1 Information of reagents used

[0041]

[0042] Table 1.2 Information of instruments and equipment used

[0043]

[0044] Example 1

[0045] A method for preparing a bismuth-based adsorption material (Bi@AC) comprises the following steps:

[0046] S1, AC carrier pretreatment: weigh a certain amount of AC, wash it with deionized water, dry it in a 60°C oven overnight, and screen out particles of appropriate size with a 10-mesh screen to obtain an AC carrier;

[0047] S2, preparation of homogeneous liquid A: 33.6 ml of anhydrous ethanol and 16.6 ml of ethylene glycol solution were mixed and added into a 100 ml polytetrafluoroethylene liner, and the mixture was stirred to obtain liquid A;

[0048] S3, preparation of homogeneous liquid B: add 0.25 g of Bi(NO3)3·5H2O to liquid A, stir magnetically for 30 min at room temperature at a speed of 500 rpm, and mix to obtain liquid B;

[0049] S4, preparation of Bi@AC: 2.5 g of AC carrier was weighed using an analytical balance and added to liquid B. The mixture was magnetically stirred at room temperature for 1 h. After mixing, the mixture was placed in a sealed stainless steel hydrothermal reactor. The reactor was placed in an oven at 200°C for reaction for 6 h. After the reaction, the reactant was obtained. The reactant was repeatedly rinsed with ultrapure water and anhydrous ethanol with the assistance of an ultrasonic cleaner, and finally dried in an oven at 60°C to obtain Bi@AC.

[0050] Example 2

[0051] A method for preparing a bismuth-based adsorption material comprises the following steps:

[0052] S1, AC carrier pretreatment: weigh a certain amount of AC, wash it with deionized water, dry it in a 60°C oven overnight, and screen out particles of appropriate size with a 10-mesh screen to obtain an AC carrier;

[0053] S2, preparation of homogeneous liquid A: 33.6 ml of anhydrous ethanol and 17 ml of ethylene glycol solution were mixed and added into a 100 ml polytetrafluoroethylene liner, and the mixture was stirred to obtain liquid A;

[0054] S3, preparation of homogeneous liquid B: add 0.20 g of Bi(NO3)3·5H2O to liquid A, stir magnetically for 30 min at room temperature at a speed of 500 rpm, and mix to obtain liquid B;

[0055] S4, preparation of Bi@AC: 1.0 g of AC carrier was weighed using an analytical balance and added to liquid B. The mixture was magnetically stirred at room temperature for 1 h. After mixing, the mixture was placed in a sealed stainless steel hydrothermal reactor. The reactor was placed in an oven at 200°C for reaction for 6 h. After the reaction, the reactant was obtained. The reactant was repeatedly rinsed with ultrapure water and anhydrous ethanol with the assistance of an ultrasonic cleaner, and finally dried in an oven at 60°C to obtain Bi@AC.

[0056] Example 3

[0057] A method for preparing a bismuth-based adsorption material comprises the following steps:

[0058] S1, AC carrier pretreatment: weigh a certain amount of AC, wash it with deionized water, dry it in a 60°C oven overnight, and screen out particles of appropriate size with a 10-mesh screen to obtain an AC carrier;

[0059] S2, preparation of homogeneous liquid A: 33.6 ml of anhydrous ethanol and 16 ml of ethylene glycol solution were mixed and added into a 100 ml polytetrafluoroethylene liner, and the mixture was stirred to obtain liquid A;

[0060] S3, preparation of homogeneous liquid B: add 0.248 g of Bi(NO3)3·5H2O to liquid A, stir magnetically for 30 min at room temperature, at a speed of 500 rpm, and obtain liquid B;

[0061] S4, preparation of Bi@AC: 4.96 g of AC carrier was weighed using an analytical balance and added to liquid B. The mixture was magnetically stirred at room temperature for 1 h. After mixing, the mixture was placed in a sealed stainless steel hydrothermal reactor. The reactor was placed in an oven at 200°C for reaction for 6 h. After the reaction, the reactant was obtained. The reactant was repeatedly rinsed with ultrapure water and anhydrous ethanol with the assistance of an ultrasonic cleaner, and finally dried in an oven at 60°C to obtain Bi@AC.

[0062] Example 4

[0063] The difference from Example 1 is that the prepared Bi@AC is ground and Bi@AC with a particle size of 10 mesh (2.00 mm) is screened for use.

[0064] Example 5

[0065] The difference from Example 1 is that the prepared Bi@AC is ground and Bi@AC with a particle size of 20 mesh (0.85 mm) is screened for use.

[0066] Example 6

[0067] The difference from Example 1 is that the prepared Bi@AC is ground and Bi@AC with a particle size of 40 mesh (0.425 mm) is screened for use.

[0068] Example 7

[0069] The difference from Example 1 is that the prepared Bi@AC is ground and Bi@AC with a particle size of 100 mesh (0.15 mm) is screened for use.

[0070] Example 8

[0071] The difference from Example 1 is that the prepared Bi@AC is ground and Bi@AC with a particle size of 200 mesh (0.075 mm) is screened for use.

[0072] Comparative Example 1

[0073] The difference from Example 1 is that the mass ratio of the added amounts of Bi(NO3)3·5H2O and the AC carrier is 1:1.

[0074] Comparative Example 2

[0075] The difference from Example 1 is that the mass ratio of the added amounts of Bi(NO3)3·5H2O and the AC carrier is 1:2.

[0076] Comparative Example 3

[0077] The difference from Example 1 is that Bi(NO3)3·5H2O is not added, and the other steps are the same, and the product after drying is AC.

[0078] Performance testing experiment

[0079] 1. Gaseous iodine adsorption experiment

[0080] The static adsorption experiment of gaseous iodine was carried out using Bi@AC in Examples 1-3, Comparative Examples 1-2, and AC in Comparative Example 3 as adsorption materials, respectively. The specific steps are as follows:

[0081] First, weigh the adsorbent material in a 5ml beaker and record the mass of the empty beaker and the beaker loaded with the adsorbent material. Then, use an analytical balance to weigh a certain amount of iodine particles and put the 5ml beaker with the adsorbent material into a larger sealed glass bottle. Finally, place the sealed glass bottle steadily in an oven set at 75°C for heating. After the adsorption time is over, take out the sealed glass bottle, use tweezers to grab the 5ml beaker and weigh it, and use formula 1.1 to calculate the mass change before and after the reaction to obtain the corresponding adsorption capacity. Among them, q e (mg / g) is the iodine adsorption capacity of the adsorbent, Δm and m s represents the added mass and initial mass of the adsorbent.

[0082]

[0083] The static adsorption test results of Examples 1-3, Comparative Examples 1-2 and AC are as follows: Figure 1 As shown in (a, b), from Figure 1 (a, b) It was observed that when the bismuth modification mass ratio was 1:10, the iodine adsorption performance of Bi@AC was the best, reaching 1.823g / g, which was 153mg / g higher than that of unmodified AC. When the bismuth modification mass ratio was adjusted to 1:2 and 1:5, the increase in the active sites of bismuth was less than the blockage of the micropore area on the surface of activated carbon, that is, the total active sites of Bi@AC showed a downward trend, resulting in a decrease in the iodine adsorption capacity of Bi@AC. This phenomenon can be explained by setting a higher modification mass ratio. When the bismuth modification ratio was increased to 1:1, the iodine adsorption performance of Bi@AC decreased significantly (iodine adsorption capacity was 1.228g / g). When the bismuth modification ratio was too low, the active sites loaded with bismuth and the microporous structure of activated carbon were not fully utilized, so that the iodine adsorption performance of Bi@AC could not be fully utilized. Through the static adsorption experiment of gaseous iodine by Bi@AC, it was found that the metal-based interaction between bismuth and iodine can improve the iodine adsorption performance of the adsorbent, and the bismuth modification mass ratio directly affects the iodine adsorption performance of Bi@AC. When the mass ratio of bismuth to activated carbon is 1:10, Bi@AC can achieve the maximum adsorption capacity (1.823 g / g).

[0084] In order to explore the effect of particle size on the iodine adsorption performance of Bi@AC, static adsorption tests were carried out using the Bi@AC prepared in Examples 4-8. The results are as follows: Figure 1As shown in Figure c, when the Bi@AC increases from 10 mesh to 20 mesh, its iodine adsorption capacity increases. It is well known that when the particle size of porous materials decreases, their specific surface area usually increases. The overall structure of the ground Bi@AC is destroyed, so that the bismuth in the internal channels and pores is exposed to the surface, increasing the surface active sites, thereby improving its iodine adsorption capacity. However, as the particle size decreases (from 20 mesh to 200 mesh), the iodine adsorption capacity of Bi@AC shows a downward trend. This is because the Bi@AC particles are placed in the form of multi-layer stacking when gaseous iodine is present. The overly dense stacking causes the mass transfer resistance of iodine molecules between Bi@AC powders to increase, hindering the capture of iodine by the internal Bi@AC active sites.

[0085] In summary, Example 1 is the best preparation process, and subsequent performance test experiments are all carried out using the Bi@AC prepared in Example 1 as the raw material.

[0086] 2. XRD structural characterization of Bi@AC

[0087] The Bi@AC in Examples 1-3, Comparative Examples 1-2, and AC in Comparative Example 3 were characterized by X-ray diffractometer. Figure 2 As shown, from Figure 2 (a) Analysis of the XRD spectrum shows that there are obvious broad peaks at 2θ=23.83 and 43.19, which are amorphous carbon peaks, indicating the amorphous structure of AC. After AC was modified by solvothermal method, the XRD spectrum was analyzed and it was found that in addition to the original broad peaks of AC, Bi@AC showed multiple diffraction peaks (2θ=27.16, 37.95, 39.61, 48.69, 56.02, 64.51). Compared with the standard spectrum of Bi (PDF#85-1329), these diffraction peaks are strong and narrow, corresponding to the (012)(104)(110)(202)(024) and (122) crystal planes of Bi, respectively. The high-intensity (012) peak indicates that the main component loaded on the activated carbon is metallic Bi, rather than Bi2O3 (corresponding to the (201) crystal plane of PDF#27-0050). The reason is that the -COOH rich in ethylene glycol has strong reducing properties and can reduce the bismuth ions in the solution to bismuth element.

[0088] The concentration of bismuth-modified solution affects its loading on activated carbon. XRD characterization was performed for different mass ratios (1:1, 1:2, 1:5, 1:10, 1:20). The results are shown in Figure 2. Figure 2As shown in (b), when the Bi:AC mass ratio is 1:10, the iodine adsorption performance of Bi@AC is the best. In addition, it is observed that the characteristic peak corresponding to Bi increases with the increase of the concentration of the modified solution, proving that there is a regularity in the loading amount of bismuth on activated carbon. The XRD characterization results show that the solvothermal method used in this study successfully loaded Bi onto activated carbon, and the controllable preparation of Bi@AC with different proportions can be achieved by adjusting the mass ratio of bismuth modified solution to activated carbon.

[0089] 3. Morphology characterization and elemental analysis

[0090] 3.1 SEM, EDS and mapping characterization of AC and Bi@AC

[0091] The Bi@AC prepared in Example 1 and the AC in Comparative Example 3 were characterized by scanning electron microscopy (SEM), EDS and mapping to observe their morphological characteristics and the elemental composition and distribution of surface metal particles. Figure 3 As shown, Figure 3 (a, b) are SEM images of AC, (c) is the SEM cross-sectional image of AC, (d, e, f) are SEM images of Bi@AC, and (g, h, i) are elemental mapping images of Bi@AC.

[0092] from Figure 3 a The AC has a well-developed honeycomb structure and intricate holes, and after electron microscopy magnification ( Figure 3 b) It is observed that there are abundant micropores around the holes, and the hole thickness is relatively thin. Figure 3 c guess that the holes are connected to the chambers, forming a complex 3D structure. After modification by solvothermal method, Figure 3 As shown in d, many randomly dispersed metal particles appear around the hole. After magnification, it is observed that ( Figure 3 e), the metal particles are loaded onto the pores, but the pores are not blocked by them.

[0093] In order to further verify the elemental composition and distribution of the material and surface metal particles, EDS and mapping characterization were performed. Figure 3 h and i are the energy dispersive spectra (EDS) of Bi@AC. The EDS results show that the loaded metal particles are Bi. It can be clearly seen from the image that the bismuth metal particles are evenly distributed without obvious aggregation and do not block the original pore structure of the activated carbon. The morphological characterization and elemental analysis results of Bi@AC are consistent with the XRD results, indicating that the present application successfully loaded metal bismuth onto activated carbon through a solvothermal method.

[0094] 3.2 SEM and EDS characterization of Bi@AC before and after adsorption of gaseous iodine

[0095] The Bi@AC prepared in Example 1 was characterized by SEM before and after adsorption of gaseous iodine to observe the changes in its surface morphology. The results are as follows: Figure 4 As shown, Figure 4 (a) and (b) are SEM images of Bi@AC before and after adsorption of gaseous iodine. It can be observed from the figure that the morphology of Bi@AC changes significantly after adsorption of gaseous iodine, and its surface and pores are covered with a large area. The loaded metal bismuth is transformed from uniformly dispersed small particles wrapped by captured iodine to aggregated large particles.

[0096] EDS characterization of Bi@AC before and after adsorption of gaseous iodine is shown in the following figure: Figure 5 As shown in the figure, it was found that the position where the elemental bismuth was loaded corresponded to the detection of iodine, proving that bismuth reacted with iodine to form bismuth-iodine compounds. In addition to the large particles formed by combining with bismuth, Figure 5 Iodine was also detected at other locations in (b) and (c). It is speculated that the iodine was formed by the activated carbon microporous structure capturing gaseous iodine to form elemental iodine. FTIR and XPS characterization are needed to analyze and clarify the substances generated after the reaction.

[0097] 4. FTIR analysis

[0098] 4.1 FTIR analysis of AC and Bi@AC

[0099] The Bi@AC prepared in Example 1 and the AC in Comparative Example 3 were characterized by Fourier transform infrared absorption spectroscopy to obtain the chemical changes before and after the modification. The FTIR spectra are shown in FIG. Figure 6 As shown, it was observed that before modification, at 1504cm -1 The weak peak at 3440 cm-1 corresponds to the stretching vibration of C=C. -1 The peaks on the left and right belong to the stretching vibration of -OH. These C=C and -OH correspond to the characteristics of aromatic lignin, and after modification, the peak at 400cm -1 Up to 700cm -1 The observed range may be Bi-O stretching vibration. The presence of Bi-O proves the loading of bismuth oxide. Figure 2 The XRD characterization results of a did not find the corresponding characteristic peak of bismuth oxide, and it is speculated that there is a small amount of bismuth oxide on Bi@AC, and it mainly exists in amorphous form. As for the XRD characterization results, it proves that the elemental bismuth is loaded on activated carbon, and the characteristic peak of elemental bismuth does not appear in the FTIR spectrum. This is because elemental bismuth exists in a metallic bond or atomic state and does not have an obvious infrared active vibration mode.

[0100] 4.2 FTIR analysis of Bi@AC before and after adsorption of gaseous iodine

[0101] FTIR analysis was performed on the Bi@AC prepared in Example 1 before and after adsorption of gaseous iodine. The results are as follows: Figure 7 As shown, Figure 7 The FTIR spectra of Bi@AC before and after adsorption of gaseous iodine. After Bi@AC adsorbs gaseous iodine, the peak at 3440 is the stretching vibration of -OH, and the peak intensity decreases significantly. -1 Up to 700cm -1 The range belongs to Bi-O stretching vibration, which also shows obvious changes. FTIR results show that -OH and Bi-O in Bi@AC play a role in the adsorption of gaseous iodine, that is, the amorphous Bi2O3 in Bi@AC participates in the capture of gaseous iodine. -OH is based on the Lewis acid-base theory, in which -OH with a lone pair of electrons acts as a Lewis base, and the iodine molecule can be regarded as a Lewis acid, and the two interact with each other. The products generated by the reaction of -OH and Bi-O with gaseous iodine cannot be accurately determined by the FTIR spectrum, and further judgment is required by XPS spectrum.

[0102] 4.3 XPS characterization of Bi@AC before and after adsorption of gaseous iodine

[0103] High-resolution X-ray photoelectron spectroscopy (XPS) was used to further explore the material changes and reaction mechanism before and after Bi@AC adsorbed gaseous iodine. The results are as follows Figure 8 As shown. In the Bi4f spectrum of Bi@AC, binding energy peaks appear at 162.1eV and 156.8eV, corresponding to the characteristic peaks of elemental bismuth at the Bi4f5 / 2 and Bi4f7 / 2 orbits, respectively; and after capturing gaseous iodine, two new peaks appear near 625eV in the full spectrum of I-Bi@AC (Bi@AC after adsorption of gaseous iodine), corresponding to the I3d orbit of iodine, indicating that gaseous iodine is successfully captured by Bi@AC; in the narrow spectrum characterization and fitting analysis of Bi and I, it is found that the Bi4f orbital spectrum of I-Bi@AC shifts from the original 162.1eV and 156.8eV to 164.5eV and 159.2eV, corresponding to Bi 3+ The characteristic binding energy of I-Bi@AC is located at 630.4eV and 618.9eV in the I3d orbital, corresponding to I - The narrow spectrum characterization and fitting analysis of Bi and I prove that elemental bismuth captures gaseous iodine by chemical adsorption to form stable BiI3.

[0104] In addition, it was found that there were small binding energy peaks at 632.1eV and 620.7eV, which correspond to the characteristic peaks of I2, proving that in addition to the gaseous iodine captured by bismuth through metal interactions, a part of the iodine was adsorbed by the activated carbon microporous structure. This is consistent with the SEM characterization results. In order to further explore the substances generated after adsorption, the O1s spectrum of Bi@AC was analyzed, and it was found that after Bi@AC adsorbed gaseous iodine, the binding energy peak at 532.8eV increased. Combined with the previous FTIR analysis, it was determined that the amorphous Bi2O3 and -OH on Bi@AC participated in the capture of gaseous iodine, and the reaction generated BiOI and I - , the reaction equations are shown in Equation 1.2 and Equation 1.3.

[0105] Bi+1.5I2=BiI3 (1.2)

[0106] 2Bi2O3+2I2=4BiOI+O2 (1.3)

[0107] 5. Characterization of the physicochemical properties of Bi@AC

[0108] The Bi@AC prepared in Example 1 and the AC prepared in Comparative Example 3 were subjected to an adsorption-desorption experiment at a temperature rise from 0°C to 800°C (at a heating rate of 10°C / min) under N2 atmosphere. The results are shown in FIG. Fig. 9 As shown in Table 2, Fig. 9 a and b are the N2 adsorption-desorption isotherms of AC and Bi@AC, respectively. Fig. 9 c and d are the pore size distribution curves of AC and Bi@AC calculated by the BJH model. Table 2 shows the pore characterization data of AC and Bi@AC.

[0109] refer to Fig. 9 a and b show that the N2 adsorption-desorption isotherms of AC and Bi@AC are more consistent with the type I isotherm, which is a common type of activated carbon. The type I isotherm is an isotherm that describes the gas adsorption characteristics of micropores (pore size <2nm), which also shows that AC and Bi@AC have rich microporous structures. The adsorption-desorption hysteresis loop appears in the range of P / P0=0.5-1.0. The reason is that capillary condensation occurs under high pressure, resulting in the adsorption-desorption isotherms not coinciding. At the same time, the start and end positions of the adsorption hysteresis of the two are basically the same, and the change trends are similar.

[0110] refer to Fig. 9c and d as well as Table 2 show that the pore size distribution of the materials before and after modification is mainly dominated by micropores of 0-2 nm. The micropore structure after modification is improved, while the mesopores and macropores are basically unchanged before and after modification, which is consistent with the results of the adsorption-desorption curve analysis, indicating that the bismuth loading before and after modification has little effect on the pore structure. The specific surface area, pore size distribution, pore volume and other important parameters are calculated by the BET model and the DFT model. The specific surface area (SSA) of Bi@AC prepared by the solvothermal method is slightly improved from 1489.9 m 2 / g increased to 1545.8m 2 / g, which is speculated to be due to the fact that the metal bismuth did not block the pores and the loaded metal bismuth had defects, thereby increasing the specific surface area of ​​the material, which is consistent with the SEM characterization results.

[0111] Table 2 Pore characterization data of AC and Bi@AC

[0112]

[0113]

[0114] 6. Kinetic model fitting of gaseous iodine adsorption on Bi@AC

[0115] The gaseous iodine adsorption experimental data of Bi@AC prepared in Example 1 were fitted by the pseudo-first-order kinetic model (PFO) and the pseudo-second-order kinetic model (PSO). The pseudo-first-order kinetic model and the pseudo-second-order kinetic model are shown in formulas (1.4 and 1.5).

[0116] ln(q e -q t )=lnq e -k1t (1.4)

[0117]

[0118] Among them, q t (g / g) and q e (g / g) are the t moment and the equilibrium adsorption amount, t (min) is the contact time, k1 (1 / min) is the first-order kinetic model rate constant, and k2 (g / mg·h) is the pseudo-second-order kinetic model rate constant. Table 3 shows the relevant parameters of the pseudo-first-order and pseudo-second-order kinetic models of Bi@AC.

[0119] Table 3 Parameters of Bi@AC adsorption kinetic model for gaseous iodine

[0120]

[0121] The fitting results of static adsorption experimental data with pseudo-first-order kinetic model and pseudo-second-order kinetic model are shown in Fig.10As shown in a, the pseudo-first-order kinetic model is more suitable for the isothermal adsorption process of gaseous iodine on Bi@AC, and its correlation coefficient R 2 =0.997, indicating that the main form of Bi@AC adsorption of gaseous iodine is physical adsorption, due to the rich microporous structure of activated carbon itself. The pseudo-second-order kinetic model mainly describes the adsorption form of the adsorbent as chemical adsorption, which is also more consistent with the form of Bi@AC adsorption of gaseous iodine. Its correlation coefficient R 2 =0.985. After modification with bismuth-based materials, the form of gaseous iodine adsorption by Bi@AC is not a single physical adsorption, but the result of the combined action of physical and chemical adsorption. Combining SEM and XPS characterization, it can be explained that after modification, bismuth is loaded on activated carbon, and metallic bismuth can interact with iodine in a metal-based manner, which enhances the iodine capture ability of Bi@AC.

[0122] The maximum adsorption capacities calculated by the pseudo-first-order kinetic model and the pseudo-second-order kinetic model were 1.99 g / g and 2.75 g / g, respectively. Compared with the experimental data, the iodine adsorption capacity calculated by the pseudo-first-order kinetic model is more reasonable, and it also proves that the iodine adsorption performance of Bi@AC can be further optimized and improved.

[0123] 7. Adsorption isotherm

[0124] To explore the change in the adsorption capacity of Bi@AC under different gaseous iodine concentrations, a static adsorption experiment was designed with the following parameters: temperature set at 75°C, adsorption time set at 4 hours, and iodine concentration set at 200-1200 mg / L. Langmuir and Freundlich adsorption isotherm models were used to fit the Bi@AC prepared in Example 1, and the Freundlich and Langmuir isotherm models are shown in formulas (1.6, 1.7).

[0125]

[0126] Among them, q e (g / g) and q max (g / g) are the adsorption capacity at equilibrium and the maximum adsorption capacity, respectively, and Ce (mg / L) is the iodine concentration in the device at adsorption equilibrium. b (L / mg) is the Langmuir constant, which is related to the adsorption heat and adsorption rate and reflects the affinity between the adsorbent and the adsorbate. K F (g / g) and n are the Freundlich adsorption constant and Freundlich index, respectively. The model fitting results and fitting parameters are shown in Fig.10 b and Table 4.

[0127] Table 4. Relevant parameters of Bi@AC adsorption isotherm model for gaseous iodine

[0128]

[0129] The fitting results of the static adsorption experimental data with the Langmuir isotherm model and the Freundlich isotherm model show that the Langmuir model is more suitable for the isothermal adsorption process of gaseous iodine on Bi@AC, and the correlation coefficient R 2 =0.988, indicating that the process of Bi@AC adsorbing gaseous iodine is a monolayer adsorption. However, the Freundlich model is not suitable for describing the process of Bi@AC adsorbing gaseous iodine. Its correlation coefficient R 2 =0.950. The adsorption capacity of Bi@AC increases with the increase of iodine concentration in the container. When the active sites of Bi@AC are fully occupied, its adsorption of iodine reaches saturation. In addition, the maximum adsorption capacity of gaseous iodine calculated by the Langmuir model is 1.85g / g, which is basically consistent with the experimental results. Combined with the fitting results of the adsorption kinetic model, the adsorption form of Bi@AC for gaseous iodine is monolayer physical and chemical adsorption.

[0130] 8. Thermogravimetric analysis of Bi@AC

[0131] Thermogravimetric analysis of Bi@AC is shown in Fig.11 As shown, through Fig.11 The thermal stability of AC, Bi@AC and I-Bi@AC in nitrogen atmosphere can be compared. First, from room temperature to 100°C, AC loses 5.9% of its mass, mainly due to water evaporation and self-decomposition. When the temperature is further increased to 800°C, the total mass loss of AC is 11wt%, which can be considered that AC has good thermal stability; Bi@AC loses 17% of its mass from room temperature to 800°C, because the loaded bismuth is lost through thermal decomposition.

[0132] There are two mass decrease stages for I-Bi@AC. The first stage is from room temperature to 100°C, and the mass of Bi@AC decreases (about 3%) due to the desorption of physically adsorbed iodine molecules. The second stage occurs from 100°C to 800°C. This process is caused by the desorption of iodine molecules and thermal decomposition of BiI3, with a total mass decrease of 68%. The sublimation temperature of BiI3 is 300°C, corresponding to a mass loss from 300°C to 800°C (about 10%).

[0133] 9. Performance comparison

[0134] The iodine adsorption capacity of Bi@AC prepared in Example 1 was compared with that of the existing reported materials (see References 1-4). It was found that the iodine adsorption capacity of Bi@AC achieved excellent performance, and its iodine adsorption capacity of 1823 mg / g exceeded that of a large number of adsorption materials reported in this field (see Table 5).

[0135] Table 5 Comparison of iodine adsorption capacity of adsorbent materials in Example 1 and existing reports

[0136] Material Type Modified Materials Iodine adsorption capacity mg / g Example 1 Activated carbon Bi 1823 Reference 1 Zeolite Silver (Ag) 355 Reference 2 UiO-66 Silver Nanoparticles (AgNP) 1260 Reference 3 Thorium-based metal-organic frameworks / 1099 Reference 4 Camphor Leaf Biochar <![CDATA[Bismuth oxide (Bi2O3)]]> 885.6

[0137] In summary, through the characterization and performance study of Bi@AC, the potential mechanism of Bi@AC adsorption of gaseous iodine can be inferred. First, gaseous iodine will enter the pores of Bi@AC and be enriched in the rich microporous structure. This is a physical adsorption process. As the adsorption proceeds, part of the gaseous iodine forms iodine elemental attached to Bi@AC, and the other part reacts with the bismuth active sites of Bi@AC (elemental bismuth and amorphous Bi2O3) to form a more stable bismuth iodine compound (BiI3 / BiOI). In addition, according to the Lewis acid-base theory, the -OH (Lewis base) of Bi@AC also participates in the capture of gaseous iodine (Lewis acid). At this time, the adsorption behavior of Bi@AC is the physical effect of the activated carbon pore structure and the structure of the chemical reaction of the active site. At the same time, it is proved that the addition of bismuth active sites improves the iodine adsorption capacity and mass transfer efficiency of Bi@AC.

[0138] The Bi@AC prepared by the method eliminates the need for a complex and energy-intensive pyrolysis method, has a short preparation cycle, and does not release non-toxic and harmless gases during the preparation process, thereby improving the convenience of preparing bismuth-based adsorption materials; relative to silver-based zeolites, metal-organic frameworks or other gaseous iodine adsorption materials, bismuth-based materials and activated carbon are more economical, and the prepared Bi@AC has a higher gaseous iodine adsorption capacity than general silver-based zeolites; through bismuth modification, the loading of the bismuth-based material provides metal active sites for the activated carbon, and the bismuth metal particles are evenly distributed without obvious aggregation, and do not block the original pore structure of the activated carbon. When adsorbing gaseous iodine, the original single physical adsorption of the activated carbon is transformed into the physical action of the activated carbon pore structure and the adsorption of the chemical action of the active sites, thereby improving the adsorption performance of gaseous iodine.

[0139] References 1-4 are as follows:

[0140] [1] Yadav, Anjali, et al. "Iodine capture by Ag-loaded solid sorbents followed by Ag recycling and iodine immobilization: an end-to-end process." Industrial & Engineering Chemistry Research 62.8 (2023): 3635-3646.

[0141] [2]Feng,Ye,et al."AgNPs-containing metal–organic frameworks for theeffective adsorption and immobilization of radioactive iodine."Journal ofChemical&Engineering Data 65.4(2020):1986-1992.

[0142] [3]Ju,Yu,et al."Synthetic Control of Thorium Metal-Organic Frameworksfor Sequencing and Sensing of Radioiodine Species."Chinese Journal ofChemistry 42.1(2024):20-28.

[0143] [4]Xie,Ying,et al."Construction of camphor leaves-derived biochar@bismuth for the capture of gaseous iodine."Chemical Engineering Science 281(2023):119205.

Claims

1. A method for preparing a bismuth-based adsorption material, characterized in that: The following steps are involved: S1, AC carrier pretreatment: weigh a certain amount of AC, wash it with deionized water, dry it in an oven overnight, and use a sieve to screen out particles of appropriate size to obtain an AC carrier; S2, preparation of homogeneous liquid A: stirring and mixing anhydrous ethanol and ethylene glycol solution to prepare liquid A; S3, preparation of homogeneous liquid B: add a certain mass of Bi(NO3)3·5H2O into liquid A, stir and mix to obtain liquid B; S4, preparation of Bi@AC: a certain mass of AC carrier is weighed and added to liquid B. After stirring and mixing, the mixture is placed in a stainless steel hydrothermal reactor, and the reactor is placed in an oven for reaction. After the reaction is completed, the reactant is obtained, and the reactant is rinsed with ultrapure water and anhydrous ethanol, and finally placed in an oven for drying to obtain Bi@AC.

2. The method for preparing a bismuth-based adsorption material according to claim 1, characterized in that: The particle size of the AC carrier is 10 mesh.

3. The method for preparing a bismuth-based adsorption material according to claim 1, characterized in that: The dosage ratio of anhydrous ethanol to ethylene glycol is 33.6:(16-17).

4. The method for preparing a bismuth-based adsorption material according to claim 1, characterized in that: The added concentration of the Bi(NO3)3·5H2O is 0.004-0.005 g / ml.

5. The method for preparing a bismuth-based adsorption material according to claim 4, characterized in that: The mass ratio of the added amount of Bi(NO3)3·5H2O and the AC carrier is 1:(5-20).

6. The method for preparing a bismuth-based adsorption material according to claim 5, characterized in that: The mass ratio of the added amount of Bi(NO3)3·5H2O and the AC carrier is 1:

10.

7. The method for preparing a bismuth-based adsorption material according to claim 1, characterized in that: The stirring condition in S3 is magnetic stirring at room temperature for 30 minutes at a rotation speed of 500 rpm, and the stirring condition in S4 is magnetic stirring at room temperature for 1 hour.

8. The method for preparing a bismuth-based adsorption material according to claim 7, characterized in that: The reaction conditions in S4 are 200° C. for 6 hours, and the drying temperature is 60° C.

9. A bismuth-based adsorption material prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the bismuth-based adsorption material according to claim 9 in adsorbing gaseous iodine.